Analysis of teaching strategies and learning challenges in Linear Algebra - Diana-Margarita Córdova-Esparza; Alethia Jimenez Piñon (CLEI Electronic Journal)
This paper provides a systematic review focused on diagnosing learning difficulties and implementing teaching strategies in the context of linear algebra. The research aims to deepen the understanding of this topic over the last decade. The study, guided by four questions, analyzed 84 articles and ultimately included 41 in the review. The search strategy was based on the PRISM protocol, and specific indicators were used. The findings indicate that most authors in the review primarily use the APOE theory and genetic decomposition for formal diagnosis of learning problems. This approach helps build knowledge frameworks, especially in vector spaces and linear transformations. A key finding is the prevalent use of digital technology in both the models and strategies proposed in these studies. This review highlights opportunities for future research in diagnosing learning problems and developing innovative, technology-integrated strategies in education.